Upaya Pengelolaan Limbah Kemasan Dalam Program Tanggung Jawab Sosial : Studi Kasus Di Industri Makanan Dan Minuman Tahun 2021-2023 - Soulthoni, Hannin PN; Itasari, Maya (Jurnal Ilmu Kesejahteraan Sosial, 2024)
Plastic waste has become an urgent environmental issue in Indonesia. This study aims to identify innovative practices implemented by food and beverage companies in Indonesia in managing plastic packaging waste, thereby serving as a reference for other companies and policymakers. This research provides an empirical contribution to understanding waste management efforts as part of corporate social responsibility (CSR) commitments. The methodology employed a qualitative approach through document analysis, involving an in-depth examination of CSR reports from companies during the 2021–2023 period. Data validity and reliability were ensured through triangulation with other relevant sources, such as sustainability reports and related publications. The analysis revealed that through technological innovation, strong partnerships, and a commitment to sustainable practices, companies successfully reduced plastic waste by up to 30% while expanding networks of Waste Banks, the Green Warmindo Program, and the Drop Box Program. Collaborations through PRAISE and IPRO have also proven effective in raising public awareness and enhancing waste management efficiency, providing valuable guidance for other companies to adopt more responsible practices. The findings of this study have significant implications for the development of more comprehensive waste management policies and encourage collaboration among governments, industries, and communities to achieve sustainable development goals.